Inovasi Pembelajaran IPS Berbasis Media ZepQuiz dalam Meningkatkan Literasi Sejarah Siswa Sekolah Dasar pada Materi Tokoh Proklamasi Kemerdekaan - Fajriah, Anisa Nurul; Fauziyah, Nafila; Wahyuningsih, Yona (Yayasan Cendekia Gagayunan Indonesia, 2025)
The level of historical knowledge among elementary school students is still low, especially regarding the material on the Proclamation of Independence. Students tend to only memorize facts and do not understand the importance of history because social studies learning is still conventional. The purpose of this study is to examine the role of ZepQuiz interactive digital media in improving elementary school students' historical knowledge related to the material on the Proclamation of Independence. Interactive digital media such as ZepQuiz is believed to increase student motivation, engagement, and understanding through interesting quizzes and direct feedback. This study used the Systematic Literature Review (SLR) method. Literature searches were conducted using Google Scholar, and the inclusion criteria were articles discussing ZepQuiz, social studies learning, interactive digital media, and historical knowledge at the elementary school level. The SLR results showed that ZepQuiz and similar digital quizzes were effective in increasing learning motivation, concept mastery, and critical thinking skills. The strongest positive impact was seen when ZepQuiz was combined with reflective learning. ZepQuiz is not only an evaluation tool, but also a means of developing historical knowledge and national values. Its effective implementation depends on the willingness of teachers to formulate questions that require advanced reasoning and facilitate a deep understanding of history. Therefore, ZepQuiz can be considered an innovation in social studies education that can strengthen elementary school students' knowledge of history and national values.